Body odour aldehyde reduction by acetic acid bacterial extract including enzymes: alcohol dehydrogenase and aldehyde dehydrogenase. (20th August 2018) - Yoshioka, N.; Kurata, K.; Takahashi, T.; Ariizumi, M.; Mori, T.; Fujisawa, H.; Kameyama, N.; Okuyama, Y.
Abstract: Objective: The major causes of unpleasant human body odour are aldehydes produced by axillary‐resident bacteria. There are many methods of body odour prevention; however, they all carry risks of destroying indigenous dermal bacteria that are necessary for the maintenance of the normal physical function of the skin. Furthermore, some methods cannot directly reduce the concentrations of substances that cause body odour. Therefore, a novel method of reducing body odour more safely and effectively is required. We focused on acetic acid bacterial enzymes, which can convert aldehydes into carboxylic acids, and investigated their effect on aldehydes and body odour. Methods: Subjects with strong body odour were recruited using screening questionnaires. Acetic acid bacterial extract including enzymes was applied to subjects' skin, and their effects were evaluated by trained panellists and by quantitative aldehyde analysis using thermal detector gas chromatography/mass spectrometry. Results: Acetic acid bacterial extract including enzymes decreased the ratio of dilution to threshold and the concentration of body odour‐producing aldehydes dropped by up to 98.7%. Conclusion: These results indicate that simply applying acetic acid bacterial enzymes on the skin can reduce the concentration of aldehydes that cause unpleasant body odour by directly converting them into carboxylic acids. Therefore, acetic acid bacterial enzymes can potentially be developed into new products that do not destroy indigenous bacteria and yet can effectively reduce unpleasant body odour. Abstract : Simply applying acetic acid bacterial extract including enzymes on the skin can reduce the concentration of aldehydes that cause unpleasant body odour. Therefore, acetic acid bacterial enzymes can potentially be developed into new products that can effectively reduce unpleasant body odour.